Human hibernating myocardium is jeopardized by apoptotic and autophagic cell death - Elsässer, Albrecht; Vogt, Achim; Nef, Holger M.; Kostin, Sawa; Möllmann, Helge; Skwara, Woitek; Bode, Christoph; Hamm, Christian; Bäumner, Jutta (Journal of the American College of Cardiology, 2004)
The aim of the present study was to objectify the loss of myocytes and the mechanism by which myocytes die in human hibernating myocardium (HHM).